Effectiveness of combined chest physiotherapy, nebulization, and therapeutic positioning in improving respiratory status among children with pneumonia: A literature review - Devi Clarisa Amanda; Imellia Harmoni Syahputri; Jihan Aqilah; Nurjanah Nurjanah; Ni Wayan Wiwin Asthiningsih (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Pneumonia remains one of the leading causes of morbidity and mortality among children worldwide, particularly in developing countries. Airway obstruction caused by retained secretions frequently impairs respiratory function, indicating the need for effective evidence-based supportive interventions in addition to pharmacological treatment. Purpose: To evaluate the effectiveness of combined chest physiotherapy, nebulization, and therapeutic positioning in improving the respiratory status of children with pneumonia. Methods: A systematic literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Relevant articles were identified through Google Scholar, PubMed, and Portal Garuda using predefined keywords and Boolean operators. Studies published between 2021 and 2025 that investigated chest physiotherapy, nebulization, positioning, or their combination in pediatric patients with pneumonia were screened according to predetermined inclusion and exclusion criteria. Eleven eligible studies were included and synthesized using narrative analysis. Results: The reviewed studies consistently demonstrated that combining chest physiotherapy, nebulization, and therapeutic positioning improved respiratory outcomes in children with pneumonia. The interventions increased oxygen saturation, reduced respiratory rate and respiratory distress, enhanced airway clearance through secretion mobilization, and improved patient comfort. Compared with single interventions, combination therapy produced more comprehensive improvements in respiratory function by simultaneously optimizing pulmonary ventilation, airway clearance, and oxygenation. Conclusion: The combination of chest physiotherapy, nebulization, and therapeutic positioning is an effective evidence-based supportive intervention for improving respiratory status in children with pneumonia. Integrating these interventions into pediatric nursing care may optimize respiratory recovery and complement pharmacological management to achieve better clinical outcomes.